(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Natural polymers are used to support or guide cellular function by mimicking the native ECM composition and microenvironment. The combination of biofunctional materials and bio-fabrication technologies like bioprinting facilitates the development of bioinspired tissue engineering constructs for regenerative medicine. Bioinks are made of materials that provide the support and structure for cells to survive, grow and proliferate. Multicomponent natural-based bioinks (e.g. alginate, collagen, gelatin, fibrin, chitosan, etc) are formulated to mimic biological composition, networks and environment for cells to grow into a matured tissues. In our recent works, we have demonstrated the importance of bioink composition and cell density in the development of biomimetic and bioinspired tissue engineering constructs, as these directly impact cellular process and tissue maturation rates. Herein, the use of natural-based materials and advanced additive manufacturing technologies for creating biomimetic tissue engineering constructs will be discussed. Ana Ferreira-Duarte is a biomedical engineer who specialised in biomimetic and bioinspired materials and engineering approaches applied in regenerative medicine. She has completed her PhD at Politecnico di Torino (Italy) in 2013 and received the Award of High Qualification Research Doctorate by Scuola Interpolitecnica di Dottorato. By late 2013, she joined the EC FP7 RESTORATION project and the Arthritis Research UK (ARUK) Tissue Engineering Centre at Newcastle University as Research Associate. She was appointed as Lecturer in Bioengineering within the School of Engineering at Newcastle University in 2015. Her current research is centred on the design of biomaterials and bioinks with advanced functional properties for the manufacturing of biomimetic 3D constructs towards understanding cellular microenvironments and studying potential therapeutic and regenerative values. She is the author of >48 papers in international peer-reviewed journals and co-led 2 patents.